2006
DOI: 10.1093/ps/85.4.593
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Trait Loci Affecting White Meat Percentage and Other Growth and Carcass Traits in Commercial Broiler Chickens

Abstract: White meat is the most economically valuable part of a broiler chicken. Increasing white meat relative to overall body size (white meat percentage, WM%) makes a broiler, gram for gram, a more valuable animal. However, accurately measuring WM% requires removing the bird from the breeding flock. Identification of markers for genomic regions associated with WM% would allow direct genetic selection on breeders. The objective of the current study was to identify genomic regions affecting WM% and other growth and ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
45
0
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(61 citation statements)
references
References 50 publications
11
45
0
5
Order By: Relevance
“…The flanking markers associated with the region of this QTL included MCW0183, ADL0180 and ADL0109. In this genomic region, 4 significant and 1 suggestive QTL for AFW were previously identified using differently independent resource populations (Ikeobi et al, 2002;McElroy et al, 2006;Park et al, 2006;Atzmon et al, 2008), which was consistent with our results.…”
Section: Qtl Analysis For Abdominal Fat Traitssupporting
confidence: 91%
See 2 more Smart Citations
“…The flanking markers associated with the region of this QTL included MCW0183, ADL0180 and ADL0109. In this genomic region, 4 significant and 1 suggestive QTL for AFW were previously identified using differently independent resource populations (Ikeobi et al, 2002;McElroy et al, 2006;Park et al, 2006;Atzmon et al, 2008), which was consistent with our results.…”
Section: Qtl Analysis For Abdominal Fat Traitssupporting
confidence: 91%
“…The flanking markers of this QTL were MCW0103 and GCT0019. This region was contained in the QTL region flanked by MCW0277 and MCW0207 reported by McElroy et al (2006), who identified a QTL affecting AFP that could explain 4.45% of the phenotypic variance in an F 2 cross between 2 commercial broiler lines. Two QTL for AFW and AFP with positive additive effects were identified at 88 and 85 cM on this chromosome.…”
Section: Qtl Analysis For Abdominal Fat Traitsmentioning
confidence: 97%
See 1 more Smart Citation
“…Therefore, genetic studies have been performed to map genes and genomic loci that affect growth, body composition (MCELROY et al 2006, CAMPOS et al 2009, and reproduction traits (TUISKULA-HAAVISTO et al 2002, SASAKI et al 2004, HANSEN et al 2005, SCHREIWEIS et al 2006. If inbred lines of diverse selection lines are used for gene mapping experiments, the probability is very high that different alleles contributing to different traits segregate in the mapping population, and thus these genetic differences can be identified.…”
Section: Introductionmentioning
confidence: 99%
“…Also there is significant positive regression coefficient between live body weight and body measurements in chickens (Olawumi, 2013). McElory et al (2006) reported that breast meat is the most economically valuable part of a broiler chicken. Increasing breast meat percentage makes a broiler, gram for gram, a more valuable animal.…”
Section: Introductionmentioning
confidence: 99%